The Relationship Of Self Esteem And Physical Fitness To Learning Achievement In Jabal Toriq Boarding School Students - Husni Mubarok; Dinar Dinangsit; Anggi Setia Lengkana (JUARA : Jurnal Olahraga, 2022)
Learning achievement is the result of evaluating students using tools after the learning process is carried out in a planned manner, both in terms of material and time. The desired learning achievement is adjusted to the types and activities in research or measurement. Whether or not participants achieve optimal performance can be influenced by several factors, including psychological factors (self-esteem) and physiological factors (physical fitness). This study aims to determine the relationship between self-esteem and physical fitness on learning achievement. The research subjects were 120 Jabal Toriq Boarding School Senior High School. This research is quantitative research with a correlational design. The study results show a significant relationship between self-esteem and physical fitness in the learning achievement of Jabal Toriq Boarding School High School students in 2021/2022, Even during the Semester Academic Year on PJOK subject matter. This is evidenced by the value of p < significance level (0.000 < 0.05) and also the correlation level of 0.892, which is included in the interval (0.80 – 1.000) powerful category